Isotope discrimination and photosynthesis of vegetation growing in the Bossoleto CO 2 spring - Miglietta, F.; Raschi, A.; Körner, C.; Vaccari, F. P. (Chemosphere, 1998)
The Bossoleto CO2 spring emits CO2 which has a stable carbon isotopic ratio (~5~3C = - 8%o). We determined ~3C on leaves of several individual species growing in Bossoleto and in a nearby control site at ambient CO,.. ~5t3C was 6% more negative in leaves of species collected from the grassland community of Bossoleto, indicating increased discrimination (A) against the heavy carbon isotope. No such changes were found in ruderal species growing in the same spring, suggesting that photosynthetic capacity was much less affected. A was substantially increased under elevated CO2 in leaves of Quercus pubescens but not in Quercus ilex, which also did not show any increase in non-structural carbohydrates. Gas-exchange measurements made on Plantago lanceolata, supported the view that photosynthetic capacity is decreased in plants grown under elevated CO: and on poor soils
Keywords: Elevated CO2; Grassland vegetation (voyant); isotopic discrimination; photosynthetic capacity

Morphological adjustments of mature Quercus ilex trees to elevated CO 2 - Hättenschwiler, S.; Miglietta, Franco; Raschi, Antonio; Körner, C. (Acta Oecologica, 1997)
It is still not known whether mature forest trees respond to increasing atmospheric CO 2 concen- trations in similar ways as seedlings do. Mature Mediterranean oaks (Qaercus ilex) growing in a CO 2 enriched atmosphere around natural CO 2 vents since the seedling stage showed a moderate, age- dependent increase in stem biomass production, but had significantly lower biomass of 6-year-old branches, decreased branching, and lower leaf area per unit branch biomass, compared to control trees at a nearby unenriched site. Our data indicate that trees in natural forest stands morphologically adjust to increasing CO 2 and reduce COz-induced initial growth stimulations. Allometric adjustments such as reduction in leaf area may be regarded as a "down-regulation" of canopy photosynthesis and may be an effective mechanism for saving water.
Keywords: allometric adjustments; biomass allocation; branch morphology; branching; leaf area; Mediterranean; natural co 2 springs; Quercus ilex